Diversidade microbiológica e rendimento da produção fermentativa de hidrogênio a partir de glicerol - Viana, Quézia Maia (2013)
The growing demand for alternative energy makes hydrogen (H2) an interesting fuel because of its high concentration of energy per unit mass. Moreover, in the future, the glycerol derived from the biodiesel industry can become an environmental liability due to the increasing production of biodiesel. Therefore, the fermentative production of hydrogen from residual glycerol is an attractive alternative because it will be possible to generate clean energy from a waste. The issue on the optimization of biological production of H2 is the selection of microbial population with an adequate diversity that improves the hydrogen yields. Techniques for pre-treatment of the inoculum select specific microorganisms to produce H2 and enrich the community with H2-producing bacteria. Therefore, these controlled environmental disturbs are widely used. Based on the above, this study aimed to: (i) select a microbiota with high potential for the production of H2 and analyse its diversity, (ii) evaluate the impact of pre-treatments on microbial diversity and hydrogen yield, (iii) evaluate the relationship between microbial diversity and hydrogen yield. Different inocula were tested at different pre-treatments (heat shock, acid shock and chloroform addition). The results show that the microbial diversity is directly related to hydrogen yield. Likewise, the impact of the pre-treatment depends on the type of inoculum. However, the highest diversity and yield were achieved with sludge withdrawn from a municipal wastewater treatment plant without any pre-treatment. In general, the pre-treatments resulted in different diversity index, which shows that the degree of disturb may not only affect the methanogenic microorganism, but also the remaining in the inoculum. The pre-treatments became redundant because only the imposed high organic load and the absence of buffer promoted reduction of pH to the optimum range for H2 production, inhibiting the methanogenic activity and improving the hydrogen yield.